False and mycoplasma‐contaminated leukemia–lymphoma cell lines: time for a reappraisal. Issue 5 (1st March 2017) - Drexler, Hans G.; Dirks, Wilhelm G.; MacLeod, Roderick A.F.; Uphoff, Cord C.
Abstract : Leukemia–lymphoma cell lines are important research tools in a variety of fields. To represent adequate model systems it is of utmost importance that cell lines faithfully model the primary tumor material and are not cross‐contaminated with unrelated cell material (or contaminated with mycoplasma). As it has been previously reported that cross‐contaminated cell lines represent a significant problem, it is of interest to know whether any improvement in the prevalence of such "false cell lines" had occurred since we called the alert in 1999. A retrospective review of our data archives covered 848 cell lines received from 1990 to 2014 from 290 laboratories in 23 countries spanning the spectrum of leukemia–lymphoma entities. Two variables were considered: authenticity and freedom from mycoplasma infection. Regarding provenance, we separately considered primary sources (original investigators having established the cell lines or reference repositories) and secondary sources. The percentages of mycoplasma‐contaminated cell lines decreased significantly over the 25‐year timespan. Among primary sourced material: mycoplasma‐contamination fell from 23% to 0%; among secondary sourced: from 48% to 21%. The corresponding figures for cross‐contamination declined from 15% to 6%, while among material obtained from secondary sources prevalence remained remarkably high, throughout the time periods at 14–18%. Taken together, our data indicate that using non‐authenticated cell lines from secondary sources carries a risk of about 1:6 for obtaining a false cell line. The use of authentic leukemia–lymphoma cell lines holds important translational value for their model character and the reproducibility of the laboratory data in the clinical arena. Abstract : What's new? Tumor cell lines are essential research tools, but a significant percentage is contaminated with other cell lines and/or mycoplasma. In our study of leukemia and lymphoma cell lines, the authors found that the incidence of mycoplasma‐contamination has decreased significantly over the past 25 years. However, cross‐contamination of cell lines still remains at an unacceptably high level, particularly among cell lines circulating unchecked between different laboratories. Researchers are urged to use authenticated cell lines, to ensure the accuracy of clinical and experimental results.